Estudio comparativo de adaptabilidad de cinco híbridos y una variedad en la producción del cultivo del brócoli (brassica oleracea l.) bajo las condiciones agroecológicas del Distrito de Lamas - Vislao Benavides, Seleni (2013)
Broccoli (Brassica oleracea L.) is an important species in human nutrition, and nutritional value lies primarily in its high content of vitamins and minerals and is an excellent source of vitamin A, potassium, iron and fiber and to be rich in carbohydrates, protein and fat (Bernal, 2004). Broccoli is high in folic acid in leaves and inflorescences so affirms its effectiveness in the prevention and control of cancer (Oleas, 2002). For your encouragement and promotion, growing broccoli, required during the growth phase mean temperatures between 20 and 24 ° C, and prefers soils with pH ranging between 6.5 and 7 and with a medium texture. Supports bad excessive salinity of soil and irrigation water (Hernán, 2001). Under the ecological conditions of district Lamas, has been encouraged since some time ago, using growing variety Calabrese broccoli, and due to inadequate crop management and climate variability that occurs in all parts of the Earth are observed in the fields of horticulture, effects on the growth stage that is impacting the physiological and metabolic actions, which transcends in decreased productivity and crop production. In this situation, we have developed this research, in order to experience the agronomic performance under the ecological conditions of the district of Lamas, and therefore determine the best performance and profitability of one or more hybrid or variety Calabres